1990
DOI: 10.3109/08916939008998418
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Autoantigenic Epitopes on Recombinant Thyroid Peroxidase Fragments Using the Polymerase Chain Reaction

Abstract: Cloned cDNA templates of thyroid peroxidase (TPO) have been used in conjunction with the polymerase chain reaction (PCR) to express selected segments of the thyroid microsomal/peroxidase antigen (TMA/TPO) as recombinant protein in E. coli. Six small, different recombinant fragments averaging 120 amino acid residues and one large fragment (269 amino acids) of TPO which together encompass 80% of the extracellular region of the molecule have been produced and autoantibody (aAb) binding sites analysed by immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Other than the use of chimeric TPO-MPO molecules (which failed to identify the immunodominant region) (35,37), most previous attempts to identify TPO autoantibody epitopes have examined polyclonal autoantibody interactions with polypeptide fragments (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) with the inherent problem of the highly conformational nature of TPO autoantibody epitopes. However, based on the putative three-dimensional model of TPO, an r-pep fragment (TPO aa residues 742-848) (23), although not defining a precise epitope, may lie in the vicinity of K713 located in the present study.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Other than the use of chimeric TPO-MPO molecules (which failed to identify the immunodominant region) (35,37), most previous attempts to identify TPO autoantibody epitopes have examined polyclonal autoantibody interactions with polypeptide fragments (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) with the inherent problem of the highly conformational nature of TPO autoantibody epitopes. However, based on the putative three-dimensional model of TPO, an r-pep fragment (TPO aa residues 742-848) (23), although not defining a precise epitope, may lie in the vicinity of K713 located in the present study.…”
Section: Figurementioning
confidence: 99%
“…It is, therefore, not surprising that identification of conformational, possibly discontinuous, TPO autoantibody epitopes (9 -11) on the native Ag has not been possible using synthetic peptides. Some polypeptide fragments of TPO are recognized by TPO autoantibodies in patients' sera (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, the wide spectrum and large size of these fragments as well as the fact that (in the native structure) polypeptides can traverse the molecule and contribute to widely separated facets on the surface of the protein have not led to deduction of the site of the immunodominant region.…”
mentioning
confidence: 99%
“…A region within amino acids 657-767 harbors a major and frequently used autoepitope (30). The last 26 amino acids of this region overlap our 20-kDa peptide.…”
Section: Figmentioning
confidence: 99%
“…Eight separate recombinant proteins representing the entire extracellular region of TPO were produced as glutathione-s-transferase (GST) fusion proteins in E. coli using the plasmid vector pGEX-2T [6] (Fig. 1).…”
Section: Autoantigen Preparationsmentioning
confidence: 99%
“…Whilst considerable progress has been made in understanding and mapping the autoantibody response to TPO [1,5,6], much less is known about recognition of TPO by the pathogenic T cells in human disease. Some studies have demonstrated evidence of sensitization to thyroid microsome preparations [7].…”
Section: Introductionmentioning
confidence: 99%